Synthesis of electro-optically active polymer composite of poly[2,2'-bis(3,4-ethylenedioxythiophene)-alt-fluorene]/hydroxypropyl cellulose showing liquid crystal structure - N. Eguchi; K. Kawabata; H. Goto (eXPRESS Polymer Letters)
Electrochemical preparation of a composite consisting of poly[2,2′-bis(3,4-ethylenedioxythiophene)-alt-fluorene] and hydroxypropyl cellulose (PEFE/HPC) was carried out. We conducted electrochemical polymerization of poly[2,2′-bis(3,4-ethylenedioxythiophene)-alt-fluorene] (EFE) as a monomer in a lyotropic liquid crystal of HPC. We used an organic solvent instead of water for lyotropic liquid crystal medium to expand the possibility of the range of monomers, although water is usually employed as a solvent for HPC for showing liquid crystallinity. Here, we employed N,N-dimethylformamide (DMF) as a solvent for HPC. Electrochemical polymerization in the polymer liquid crystal was carried out to obtain a polymer film with liquid crystal order. The polymer film thus prepared exhibited optical activity. Fourier transfer infrared (FT-IR) absorption spectroscopy reveals that the film is a composite consisting of HPC and polymer. The composite PEFE/HPC thus prepared in HPC/DMF system showed electrochromism.